Efeitos da exposição materna pré e pós-natal ao glifosato no sistema reprodutor da prole de camundongos machos - Teleken, Jakeline Liara (2018)
Increased use of pesticides worldwide, including in Brazil, has raised awareness of the toxic effects of pesticide exposure. Among the pesticides, glyphosate herbicide is the most commercially active ingredient in the world. Exposure to glyphosate has been associated with the development of health problems in humans and animals, such as cancer, birth defects, cardiovascular problems, changes in the central nervous system, reproductive system, among others. In addition, recent studies have shown that glyphosate acts as an endocrine disrupter because of its actions on the hormonal system. Exposure to endocrine disrupters at critical stages of development, such as the neonatal period, can lead to fetal programming predisposing to disease development in adult life. Thus, the objective of this study was to evaluate the effects of maternal exposure to glyphosate, during pregnancy and lactation, on the dams and reproductive system of male offspring in adulthood. Female C57Bl6 received 0.5% glyphosate (ROUNDUP Original DI®) in drinking water (GF group) or pure water (CTL group) during pregnancy and lactation. Male offspring were separated into two groups CTL-F1 and GF-F1, according to the administration or not of glyphosate for the dams. Both groups received standard diet and water ad libitum during the entire experiment. Body weight, water and food intake were evaluated weekly, and the testis descent was monitored at 21 days of age to evaluate the onset of puberty. At 150 days the offspring mice were euthanized and blood was collected for subsequent plasmatic analyzes. The reproductive organs were removed and weighed. The epididymis was used for sperm count. The pituitary was removed and used to determine the protein expression of LH. The right testis was fixed in ALFAC and used for histomorphological analysis, and the left testis was used for intratesticular testosterone assay. Maternal exposure to glyphosate did not alter body weight, food and water intake, and weight of reproductive organs of male offspring. However, there was a delay in the onset of puberty and a decrease in the number of spermatozoa in the tail of the epididymis in the GF-F1 group in relation to the CTL-F1 group. Although in the histological analysis no alteration was found in the animals of the GF-F1 group, these animals showed a decrease in the height of the seminiferous epithelium in relation to the CTL-F1 group. In relation to hormonal dosages, intratesticular testosterone levels was higher in the GF-F1 group than in the CTL-F1 group, although the testosterone plasma levels had similar values in both groups. LH was increased both in the plasma and in the pituitary GF-F1 group, whereas FSH was similar between the CTL-F1 and GF-F1 groups. Our results suggest that maternal exposure to glyphosate led to fetal programming that culminated with changes in the reproductive system in adult life of male offspring.